"Jubilee" [compact disc] - Watson, Willie, 1979-; Ferrell, Sierra; Staples, Mavis (ATO Records, 2023)
Old Crow Medicine Show celebrates their 25th anniversary with the release of a brand-new album. It encompasses everything from jug-band tunes to Irish folk songs to exultant gospel jams and includes collaborations with Mavis Staples, Sierra Ferrell, and band co-founder Willie Watson.